Neurological Deafness Prevalence Based on Diabetes Mellitus and Gender - Wirayudha, Yan; Kurniati, Yuni Prastyo; Nugraheni, Fladea Eka (Journal La Medihealtico, 2024)
Neurological deafness or sensorineural hearing loss is a hearing loss caused by damage to the cochlea, vestibulocochlear nerve (N.VIII), or the nerve pathways that connect the ear to the brain. Indonesia is part of 4 countries in Asia that have a high prevalence of sensorineural hearing loss, namely 4.6%. Neurological deafness is caused by several factors, including age, genetic factors, and environmental factors. Some studies also show that hypertension, diabetes, and hypercholesterolemia can predispose to neural deafness. One of the complications caused by diabetes mellitus is hearing loss caused by microangiopathy. Gender has also been linked as a risk factor that causes neural deafness. This study aims to determine the relationship between diabetes mellitus and gender with the incidence of neurological deafness in adult patients in the city of Surakarta. This study used secondary data from adult neurologically deaf patients aged >18 years who had diabetes mellitus. This research design uses cross sectional. The total sample size was 67 respondents. The data obtained were analyzed using the chi-square test and logistic regression test. The results of this study stated that there was a relationship between diabetes mellitus and the incidence of neural deafness (p=0.000), there was a relationship between gender and the incidence of neural deafness, namely male gender (p=0.025). A significant relationship was found between diabetes mellitus and gender and the incidence of neurological deafness in adult patients in the city of Surakarta.